Nonconvulsive Status and Ictal–Interictal Continuum in Neurology Intensive Care Unit - Miny Susan Abraham; Nikhil Gladson (Archives of Medicine and Health Sciences)
Analysis of spontaneous electroencephalogram activity is an essential method in the evaluation of patients with impaired consciousness in both acute care and chronic settings. It continues to be the only method that allows the bedside monitoring of both immediate and long-term cortical functioning associated with the conscious or unconscious state. We report three case scenarios: (1) encephalopathy with periodic discharges in chronic kidney disease patients; (2) nonconvulsive status in poststroke patient after 2 weeks; and (3) nonconvulsive status in a patient with chronic alcoholic intake.